Incorporation of iron oxide into CNT/GNF as a high performance supercapacitor electrode - Ramli, Nurul Infaza Talalah (Elsevier, 2018)
CNT/GNF/Fe₂O₃ ternary composites were synthesized via a simple hydrothermal route. The electrochemical findings reveal that the incorporation of iron oxide (Fe₂O₃) into CNT/GNF (174 F g⁻ˡ) boosts the specific capacitance (Cs) to 307 F g⁻ˡ at 10 mV s⁻ˡ. The system also shows good capacity retention, as it maintained 92% of its original capacitance after 200 cyclic voltammetry cycles. Physicochemical characterization shows that Fe₂O₃ was anchored randomly on the CNT/GNF sidewalls, forming a network for facile ion diffusion. The improved supercapacitance of CNT/GNF/Fe₂O₃ can be ascribed to the synergistic effect of the double-layer capacitance of CNT/GNF and the pseudocapacitance of Fe₂O₃.